EVALUASI KEBIJAKAN PEMERINTAH TENTANG PELATIHAN BERBASIS KOMPETENSI DI KOTA BANDUNG PADA TAHUN 2022-2023 - Rosiana, Ida; Bintari, Antik (Universitas Djuanda, 2025)
The city of Bandung is one of the cities with the highest open unemployment rate in West Java. One of the causes is the suboptimal absorption of job vacancies. To address this issue, the Bandung City Manpower Office (Disnaker) organizes competency-based training. However, in reality, it has not had a significant impact on solving employment problems, such as the lack of proper synchronization between the types of training and the skills needed by companies, as well as the implementation not fully adhering to the Indonesian National Work Competency Standards (SKKNI). Therefore, an evaluation is needed to assess the extent to which the objectives of this activity have been achieved. This research uses a descriptive method. Data collection techniques include observation, interviews, and documentation. The primary and secondary data used in this study were obtained from interviews with research informants. The researcher adopts the activity evaluation theory by the Organisation for Economic Co-operation and Development (OECD) as a reference in the analysis, which consists of criteria such as relevance, coherence, effectiveness, efficiency, impact, and sustainability. Based on the researcher’s findings, competency-based training has been implemented. However, improvements are still needed in several areas, including the lack of alignment between training types and company needs, incomplete adherence to SKKNI guidelines, and the absence of follow-up after the training ends. Other challenges include insufficient funding, inadequate infrastructure and technology, and the lack of participant distribution to companies.